ANALISIS KONFORMITAS NEGATIF KELOMPOK TEMAN SEBAYA PADA SISWA - Siska Tutiana; Dewang Sulistiana; Feida Noorlaila Isti’adah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to describe the Negative Conformity of Peer Groups among HighSchoolStudentsinTasikmalayaRegencybasedonaspectsandindicators,differences based on gender, based on class level, and to design guidance andcounselingservicesaspreventiveservicestoreducenegativepeergroupconformity to students. This study uses a quantitative descriptive method to revealthenegativeconformitypictureofpeergroups.Thepopulationinthisstudyishighschool students in Tasikmalaya Regency which consist of several schools. Thesample in this study was SMA Tasikmalaya high school students, totaling 427students, who were taken by accidental sampling. The results of this study, ingeneral, the negative conformity of peer groups among high school students inTasikmalayaRegencyisinthelowconformitycategoryof92%(392students).Thehighest aspect is agreement while the lowest aspect is obedience. Based on classlevelandgender, thereisnodifferencewiththesig.0.004whichmeansthereisnosignificant difference between the negative conformity of male and female studentsin SMA Tasikmalaya Regency. The limitations of this study are that it is still notable to test group guidance services as preventive services to reduce negative peergroup conformity, and the formulation and implementation plans for the servicesattachedarestill limited.Keywords:conformity,peergroups,students